Connections between the basal I1 "growth" fault and 〈c + a〉 dislocations. (1st January 2015) - Agnew, S.R.; Capolungo, L.; Calhoun, C.A.
Abstract: Recently published experimental results have suggested a connection between the I1 basal stacking fault and the non-basal 1 3 〈 1 1 2 ¯ 3 〉 (i.e. 〈 c  +  a 〉) dislocation, particularly in Mg–Y and Mg–Y–Zn alloys. Deformed Mg–Y alloys contain more 〈 c  +  a 〉 dislocations and I1 faults than pure Mg, and the I1 fault energy has been shown to be significantly reduced by the addition of Y solute atoms using ab initio modeling. The TEM evidence of a possible connection between the two crystal defects is reanalyzed to reveal: (i) a non-planar dissociation of the pyramidal 〈 c  +  a 〉 edge dislocation into the basal plane, resulting in an I1 fault bounded by 1 6 〈 2 0 2 ¯ 3 〉 partial dislocations; and/or (ii) a new source mechanism involving nucleation of the pyramidal 〈 c  +  a 〉 dislocation from a pre-existing I1 fault. The former reaction is energetically favorable, but non-conservative. The latter is shown to be energetically conceivable for a wide range of fault geometries. The concepts hypothesized in this paper provide explanations for the frequent TEM observation of rectilinear, edge 〈 c  +  a 〉 dislocations in Mg alloys, as well as a possible explanation for the yield strength anomaly observed in Mg and Mg alloy single crystals. Implications for radiation damage in hexagonal close packed metals are also suggested.